PENERAPAN METODE PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMK - Arlin Yuniyanti Silalahi; M. Afrilianto; Adi Nurjaman (IKIP Siliwangi, 2023)
This research is motivated by the lack of understanding of students in learning mathematics. So that the Problem Based Learning approach was chosen by means of peer tutor discussions. The research process was carried out in three cycles, where each cycle includes 4 stages, namely: 1) the student orientation stage on the problem 2) the student organization stage, 3) the stage of guiding the investigation, 4) the stage of developing the work, 5) the analysis and evaluation stage. Data was collected by purposive sampling, namely 10 students of class XI SMK Karya Bhakti Pusdikpal. Technical analysis of the data is seen from the learning outcomes or the scores obtained from three cycles with a minimum limit of 85% reaching the KKM score of 75. The results obtained from the implementation of the research show an increase, where the student's score has increased from an average of 64.5 to 81.4 and becomes 85.6. Therefore, it can be concluded that the application of the Problem Based Learning Method by means of peer tutor discussions can improve students' mathematics learning outcomes and teachers should use this method to increase student activity in understanding the concepts of mathematics learning.